A model for the intensity of fishing gear. (9th June 2021) - Kuczenski, Brandon; Vargas Poulsen, Camila; Gilman, Eric L.; Musyl, Michael; Winkler, Bri; Geyer, Roland
Abstract: Industrial fishing, instrumental in feeding the world's population while providing a livelihood to many people, also presents a variety of hazards to the health of the ocean, including the accumulation of derelict fishing gear. Although direct evidence of harm from derelict gear is abundant, efforts to quantify and assess the threats posed by it are confounded in part by the tremendous diversity of fishing gear and techniques. In this paper, we advance a novel analytic framework for describing the use of fishing gear that can be applied to evaluate the environmental impacts that arise from fishing activity. We model fishing as a unit process comprising three successive characterizations, each of which can be observed and validated independently: the intensity of fishing effort, the material intensity of gear, and the intensity of the environmental effect. We present the method as an open‐source computation system with a library of gear models that can be reviewed and extended by the research community. We apply the program to estimate the generation of derelict gear for several different gear types and discuss how it can be expanded to advance the understanding of the impacts of industrial fishing at the global scale. This article met the requirements for a Gold–Gold JIE data openness badge described at http://jie.click/badges .